1995
DOI: 10.1073/pnas.92.17.8011
|View full text |Cite|
|
Sign up to set email alerts
|

An integral membrane component of coatomer-coated transport vesicles defines a family of proteins involved in budding.

Abstract: We have isolated a major integral membrane protein from Golgi-derived coatomer-coated vesicles. This 24-kDa protein, p24, defines a family of integral membrane proteins with homologs present in yeast and humans. In addition to sequence similarity, all p24 family members contain a motif with the characteristic heptad repeats found in coiled coils. When the yeast p24 isoform, yp24A, is knocked out in a strain defective for vesicle fusion, a dramatic reduction in the accumulation of transport vesicles is observed. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
244
2
3

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(253 citation statements)
references
References 37 publications
4
244
2
3
Order By: Relevance
“…All p24 family members are type I membrane proteins and share a common structure, with a short cytoplasmic tail containing binding signals for COP I and COP II coat complexes and a luminal domain with potential secretory cargo binding capabilities Sohn et al, 1996;Dominguez et al, 1998;Muniz et al, 2000). Proteomics analysis revealed that p24 family members are major constituents of COP I-coated vesicles (Stamnes et al, 1995). Their involvement in COP I vesicle formation was identified in vitro by using liposomes with Golgi-like lipid composition.…”
mentioning
confidence: 99%
“…All p24 family members are type I membrane proteins and share a common structure, with a short cytoplasmic tail containing binding signals for COP I and COP II coat complexes and a luminal domain with potential secretory cargo binding capabilities Sohn et al, 1996;Dominguez et al, 1998;Muniz et al, 2000). Proteomics analysis revealed that p24 family members are major constituents of COP I-coated vesicles (Stamnes et al, 1995). Their involvement in COP I vesicle formation was identified in vitro by using liposomes with Golgi-like lipid composition.…”
mentioning
confidence: 99%
“…In a yeast strain defective for vesicle fusion, a p24 knockout reduced the number of COPI-coated vesicles (Stamnes et al 1995). These data suggested that type I transmembrane proteins represent membrane receptors for coatomer and are actively required for the formation of COPI vesicles (Stamnes et al 1995;Sohn et al 1996). Surprisingly, however, in yeast the deletion of all p24 proteins showed only a reduction in the rate of transport of some cargo proteins (Springer et al 2000).…”
Section: Coat Recruitmentmentioning
confidence: 69%
“…p24 proteins are present in COPI vesicles in amounts stoichiometric to coatomer (Sohn et al 1996). In a yeast strain defective for vesicle fusion, a p24 knockout reduced the number of COPI-coated vesicles (Stamnes et al 1995). These data suggested that type I transmembrane proteins represent membrane receptors for coatomer and are actively required for the formation of COPI vesicles (Stamnes et al 1995;Sohn et al 1996).…”
Section: Coat Recruitmentmentioning
confidence: 80%
See 1 more Smart Citation
“…Furthermore, the binding of the plasma membrane AP-2 adaptors to tyrosine-based motifs was shown to be strengthened upon clathrin coat formation, suggesting that cargo recognition and coat assembly are indeed coupled (49). By analogy, it has been proposed that some members of the p24 family, which can bind via their dilysine motifs to coatomer in vitro and are found in COPI-coated vesicles (13,18,27), may act in the donor membrane as cargo receptors and coatomer and/or ARF receptors. In fact, p23 and p24 cytoplasmic tails attached to artificial liposomes of physiological lipid composition appear sufficient to recruit coatomer in the presence of ARF-GTP to these membranes (21).…”
Section: ⑀-Cop-depleted Copi Binding To Membranes and Sorting Signalmentioning
confidence: 99%